Molecular Surveillance of Natural Focal Diseases Causative Agents in the Stavropol Territory in 2016–2021 - E. V. Chekrygina; A. S. Volynkina; O. A. Zaitseva; Ya. V. Lisitskaya; I. V. Tishchenko; O. A. Gnusareva; D. V. Rostovtseva; E. I. Vasilenko; N. O. Tkachenko; O. V. Vasilyeva; K. A. Purmak; N. I. Solomashchenko; et al. (Эпидемиология и вакцинопрофилактика)
Relevance. Molecular surveillance, aimed at obtaining up-to-date information on the genetic variants of pathogens circulating in the studied region, is an important element of the surveillance of natural focal infections (NFIs). The Stavropol Territory is one of the main recreational regions in the Russian Federation; it is endemic for a number of NFIs, including: Crimean-Congo hemorrhagic fever (CCHF), Q fever, tularemia, Lime disease, etc.The aim of the work is is genomic profiling of NFIs causative agents circulating in the Stavropol Territory in 2016-2021.Materials and methods. Microbial strains and samples of field and clinical material containing genomic DNA/RNA of pathogens were used as material for the study. Genetic typing of strains and isolates of DNA/RNA NFIs causative agents was performed by MLVA (Francisella tularensis and Coxiella burnetii) and genome fragment sequencing (Crimean-Congo hemorrhagic fever virus, West Nile virus, orthohantaviruses, Borrelia burgdorferii s.l., Ricckettsia sp.).Results. As a result of molecular genetic typing in the ST in 2016-2021 confirmed circulation of strains of F. tularensis of genetic subgroups B.I, B.III, B.VI, genetically identical strains of C. burnetii (VNTR-профиль 4-6-6-4-7-6-3-12-3-11), rickettsia belonging to 5 species: R. raoultii, R. aeschlimannii, R. slovaca, R. massiliae, R. helvetica , Borrelia belonging to the species: B. afzelii, B. garinii, B. miyamotoi, B. bavariensis, B. lusitaniae, B. valaisiana, RNA isolates of the CCHF virus of the Europe-1 and Europe-3 genetic lines, Tula orthohantaviruses, West Nile virus genotype 2. For the first time on the territory of the CT, in insectivore lung samples, RNA isolates of orthohantavirus genetically close to Camp Ripley virus (RLPV) were detected.Conclusions. New data have been obtained on the distribution of genetic variants of NFIs causative agents in the S, also in the recreation areas. Genetic structure of the population of NFIs causative agents in the ST in 2016-2021 did not change significantly, which indicates the relative stability of the natural foci of NFIs in the region.